Volunteerism: 'Community Mothers' in Action - Downie, Jill; Clark, K.; Clementson, K. (eContent Management Pty Ltd, 2005)
Volunteers represent a growing, but often undervalued, sectio of service delivery in many areas in the community, particularly in health care. This paper is centred on volunteers' perceptions and experiences of home visiting gained through the implementation of the Community Mothers (CM) program in Western Australia (WA). Further, the paper aims to inform debate about the issue of professional versus non-professional home visitors and offers a perspective on the issue that may provide direction for policy makers and practitioners. This qualitative study involved individual telephone interviews with a volunteer sample of 12 participants, purposefully selected. Transcript data from each interview was examined and coded utilising an adapted method of content analysis described by Burnard (1991). Three main themes emerged in the findings as to why volunteers became involved in the Community Mothers Program: (1) Empathic concern; (2) Contribution to community life; and (3) Lifecourse issues and personal development. With experiences of volunteers in home visiting, four main themes reflected the participants views: (1) Facilitating client empowerment; (2) Facilitating personal empowerment; (3) Promoting social connectedness, and (4) Enabling goal setting. Although programs such as the Community Mothers Program aim to benefit and support mothers in the parenting role it is clear that there are benefits that emerge also for individual volunteer, such as increased self-esteem, self-efficacy and satisfaction. Hence, measuring the overall outcomes that result from such a program remains a major challenge.